2019
DOI: 10.1101/606350
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Virulence Index: A Metric for Quantitative Analysis of Phage Virulence

Abstract: 37Background: One of the main challenges in developing phage therapy and manufacturing phage 38 products is the reliable evaluation of their efficacy, performance and quality. Since phage virulence is 39 intrinsically difficult to fully capture, researchers have turned to rapid but partially inadequate 40 methods for its evaluation. 41Materials and Methods: The present study demonstrates a standardized, quantitative method to 42 assess phage virulence based on three parameters: the Virulence Index (V P ) -quan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 51 publications
(1 reference statement)
0
22
0
Order By: Relevance
“…The effects of nutritional environment were briefly investigated by Storms et al. in the development of the virulence index, a method of quantifying phage virulence relative to the natural host growth rate [ 39 ]. In the study of [ 39 ] it was also shown that temperature had an effect on phage virulence alongside growth media, as well as the same phage having different dynamics in secondary host strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of nutritional environment were briefly investigated by Storms et al. in the development of the virulence index, a method of quantifying phage virulence relative to the natural host growth rate [ 39 ]. In the study of [ 39 ] it was also shown that temperature had an effect on phage virulence alongside growth media, as well as the same phage having different dynamics in secondary host strains.…”
Section: Discussionmentioning
confidence: 99%
“…in the development of the virulence index, a method of quantifying phage virulence relative to the natural host growth rate [ 39 ]. In the study of [ 39 ] it was also shown that temperature had an effect on phage virulence alongside growth media, as well as the same phage having different dynamics in secondary host strains. These are all factors that need to be taken into consideration when optimising phage cocktails for use outside of the lab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two virulence metrics the virulence Index (VP) and MV50 were calculated based on the protocol described by Storms and others 47 . Briefly, bacterial cultures were grown to exponential phase and then adjusted (as described for lysis period) to an optical density equivalent to 1 x 10 8 cfu/mL.…”
Section: Methodsmentioning
confidence: 99%
“…In comparing host growth using AUC as a metric for relative virulence, two sets of limits were also used. Given the demonstrated inadequacy of µ max in determining V R in non-lytic viral infections, an alternative approach is to calculate a percent inhibition (PI AUC ) of host growth [15][16][17][18] based on AUC for infected (AUC infected ) and uninfected controls (AUC CTL ).…”
Section: Accessmentioning
confidence: 99%